The effect of different surface characterization on bonding strength of maxillofacial silicone elastomer to two different framework materials. - Zhala Meran; Omar Kamaran Anwar (Erbil Dental Journal)
Background and Objective: The objective of the study was to compare the bonding strength between silicone elastomer and two types of framework materials (acrylic resin and metal chrome cobalt) with different surface characterization. Methods A-2186 silicone elastomer was bonded with A-330-G primer to two group of framework materials (acrylic resin and metal chrome cobalt). Each group was subdivided into 4 different surface characterization (Polished surface as a control, Sandblasted surface by aluminum oxide media 250 micron, Polished surface with retentive holes, Surface with retentive holes and sandblasted by aluminum oxide media 250 micron). The samples were prepared with the dimension of (75x 10x 3 mm). All the test groups were subjected to 1800 peel strength test on Hounsfeild universal testing machine (HT-400). The test was carried out according to the ASTM D-903 specifications. The obtained results were then subjectedto statistical analysis using Stat Graph 5.1 and the statistical significance was set at 5% level of significance. Result The result showed no significant difference between polished acrylic and sandblasted acrylic surface. However, a significant improvement in bonding strength was observed when acrylic surface was grooved with retentive holes (with and without sandblast surface characterization). However, a significant effect was seen when the surface of metal chrome cobalt was sandblasted with aluminum oxide media compared to polished metal. Additionally, grooves also improved the bonding strength. Furthermore, superior effects were seen when the grooves where sandblasted. Lastly, Intergroup comparison showed superior bonding strength between metal chrome cobalt and silicone compared to acrylic resin and silicone for all surface characterization. Conclusion Within the limitations of the present study, it can be concluded that: There is no significant difference when acrylic surface was sandblasted. However, retentive holes improved the bonding strength between acrylic and silicone. While sandblast improved the bonding strength between metal and silicone elastomer. Lastly, metal bond better to silicone than acrylic resin for all tested groups.